Moderate‐to‐vigorous physical activity modifies the relationship between sedentary time and sarcopenia: the Tromsø Study 2015–2016. Issue 4 (1st June 2021) - Johansson, Jonas; Morseth, Bente; Scott, David; Strand, Bjørn Heine; Hopstock, Laila A.; Grimsgaard, Sameline
Abstract: Background: Sarcopenia is an age‐related muscle disease primarily characterized by reductions in muscle strength that increases the risk of falls, fractures, cognitive impairment, and mortality. Exercise is currently preferred in prevention and treatment, but it is unknown how different habitual physical activity and sedentary behaviour patterns associate with sarcopenia status. The purpose of the present study was to compare associations of these patterns with probable sarcopenia in older adults. Methods: In 3653 community‐dwelling participants (51% women) aged 60–84 years from the seventh survey of the Tromsø Study, we assessed objective physical activity and sedentary behaviour collected over 8 days (ActiGraph wGT3X‐BT Accelerometer), grip strength (Jamar+ Digital Dynamometer), five‐repetition chair stands, and self‐reported disease. We combined tertiles of sedentary (SED) time and moderate‐to‐vigorous physical activity (MVPA) to create nine different activity profiles (SEDHIGH, SEDMOD, and SEDLOW combined with MVPAHIGH, MVPAMOD, or MVPALOW ). Multiple logistic regression models were used to examine how these profiles associated with probable sarcopenia, defined by low handgrip strength and/or slow chair stands time according to the revised European Working Group on Sarcopenia in Older People criteria. Results: Probable sarcopenia was present in 227 (6.2%) participants. Men with probable sarcopenia had on average 35.3 min more SED time and 20 min less MVPA compared with participants without sarcopenia ( P < 0.01 for all), while women with probable sarcopenia only had 18 min less MVPA ( P < 0.001). Compared with the SEDHIGH –MVPALOW reference activity profile (714.2 min SED/day and 10.4 min MVPA/day), the SEDHIGH –MVPAMOD profile (697.1 min SED/day and 31.5 min MVPA/day) had significantly lower odds ratio (OR) for probable sarcopenia (OR 0.17, 95% confidence interval [CI] 0.08–0.35), while the SEDLOW –MVPALOW profile (482.9 min SED/day and 11.0 min MVPA/day) did not (OR 0.72, 95% CI 0.47–1.11). These findings were not influenced by age, sex, smoking, or self‐reported diseases, and higher levels of MVPA did not further decrease ORs for probable sarcopenia. Conclusions: Older adults who achieve moderate amounts of MVPA have reduced odds for probable sarcopenia, even when they have high sedentary time. Those with low sedentary time did not have reduced odds for probable sarcopenia when they also had low amounts of MVPA. These findings need confirmation in longitudinal studies but suggest that interventions for preventing sarcopenia should prioritize increasing MVPA over reducing sedentary behaviour.